Extra-sectoral drivers of forest change - Lobovikov, M.; German, L.; Jaeger, D.; Kengen, S.; Konijnendijk, C.; Buttoud-Kouplevatskaya, I.; Komarudin, Heru; McClain, K.M.; Nascimento, J.R.; Schoneveld, George C.; Stadt, J.J. (IUFRO, 2010)
This chapter provides a brief summary of the extra-sectoral drivers shaping forests worldwide. Extra-sectoral drivers are driving forces of forest change that originate from beyond the forest sector and that affect forests and their social, economic, and ecological functions. Recent increases in demand for raw materials, especially in emerging economies, increased commodity prices, and the increased scale and pace of extra-sectoral investments in the forest frontier, have contributed to extra-sectoral influences eclipsing sectoral developments as key drivers of forest landscape transformation. This chapter gives a brief overview of extra-sectoral pressures on forests and the effects these have had on forest-dependent communities.